Combined effect of konjac glucomannan addition and ultrasound treatment on the physical and physicochemical properties of frozen dough. (15th June 2023) - Lu, Peng; Guo, Jinying; Fan, Jiawei; Wang, Ping; Yan, Xiang
Highlights: The sequence of KGM and ultrasound modified frozen dough through different way. KGM and ultrasound had a positive influence on the hydration, rheology of frozen dough. KGM and ultrasound improved the gluten network structure of frozen dough. KGM and ultrasound treated samples showed soft textural properties. Abstract: The effects of dual sequential modification using konjac glucomannan and ultrasound treatments at power densities of 15–37.5 W/L on the hydration, rheology and structural characteristics of frozen dough were investigated in this study. The results revealed that the konjac glucomannan and ultrasound treatments improved the textural properties of frozen dough, but had a negative impact on its viscoelasticity. Furthermore, konjac glucomannan and ultrasound treatments increased the content of free sulfhydryl group and disulfide bond, as well as improved the freeze tolerance of dough. The results exhibited that the enthalpy of frozen dough decreased by 20.42 % compared with the frozen blank control dough under ultrasonic power density of 22.5 W/L. The network structure of frozen dough treated by konjac glucomannan and ultrasound was more ordered and integral than that of frozen blank control dough. These results provide valuable knowledge on the application of konjac glucomannan and ultrasound to frozen wheat-based foods.